2014
DOI: 10.1140/epjc/s10052-014-2871-x
|View full text |Cite
|
Sign up to set email alerts
|

Large $$N$$ N approach to Kaon decays and mixing 28 years later: $$\Delta I=1/2$$ Δ I = 1 / 2 rule, $$\hat{B}_K$$ B ^ K , and $$\Delta M_K$$ Δ M K

Abstract: We review and update our results for K → ππ decays and K 0 -K 0 mixing obtained by us in the 1980s within an analytic approximate approach based on the dual representation of QCD as a theory of weakly interacting mesons for large N , where N is the number of colors. In our analytic approach the Standard Model dynamics behind the enhancement of ReA 0 and suppression of ReA 2 , the socalled I = 1/2 rule for K → ππ decays, has a simple structure: the usual octet enhancement through the long but slow quark-gluon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
103
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 122 publications
(380 reference statements)
9
103
0
Order By: Relevance
“…While, the improvement on the estimate of isospin corrections, final state interactions (FSI) [10][11][12][13][14][15] and the inclusion of NNLO QCD corrections could in principle increase ε /ε with respect to the one in (1.1), it is rather unlikely that values of ε /ε violating the upper bound in (1.3) will be found within the SM. After all, until now, lattice QCD confirmed most of earlier results on K meson flavour physics obtained in the large N approach (see [2,16]). …”
Section: Jhep04(2016)071 1 Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…While, the improvement on the estimate of isospin corrections, final state interactions (FSI) [10][11][12][13][14][15] and the inclusion of NNLO QCD corrections could in principle increase ε /ε with respect to the one in (1.1), it is rather unlikely that values of ε /ε violating the upper bound in (1.3) will be found within the SM. After all, until now, lattice QCD confirmed most of earlier results on K meson flavour physics obtained in the large N approach (see [2,16]). …”
Section: Jhep04(2016)071 1 Introductionsupporting
confidence: 85%
“…• ∆M K is uniquely suppressed with the suppression increasing with increasing κ ε and M Z : Large N approach [16] indicates that long distance contributions enhance this ratio by roughly 20%. First lattice calculations [75] are still subject to large uncertainties and also the large error in (5.14) precludes any definite conclusions at present whether NP should enhance or suppress this ratio.…”
Section: Jhep04(2016)071mentioning
confidence: 98%
“…It affects the value of the K 0 → π 0 π 0 transition through the dominant QCD Q 6 penguin operator, which is one of the sources of uncertainties in the determination of ð ϵ 0 ϵ Þ CP [18], for a recent review see [19]. In chiral perturbation theory (ChPT) [2,20,21] the π 0 − η mixing angle occurs already at order p 2 and was first evaluated to order p 4 in the context of K l3 form factors in [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has therefore been studied with many different theoretical methods [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In recent years these efforts have been extended to include lattice QCD studies, with recent results reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Next-to-leading order contributions were considered within the large N c approach in Refs. [9][10][11]. The potentially important role of the trace anomaly in weak K decays, especially in regard to the ΔI ¼ 1=2 rule, was discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%